PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DISERTAI TEHNIK PETA PIKIRAN (MIND MAPPING) PADA POKOK BAHASAN PERSAMAAN GARIS LURUS DI KELAS VIIID SMP NEGERI 14 JEMBER SEMESTER GANJIL TAHUN A - Wijayanti, Weny; Setiawan, Toto' Bara; Dafik, d (Kadikma, 2015)
Abstract. The purpose of this research is to increase students’ activities and learning achievement score. This research implemented Student Teams Achievement Division methods by using Mind Mapping. This research type is a Classroom Actions Research (CAR) of two cycles, there are two classes in each cycles. In the first cycle the research taught rectangular topic, whereas in the second cycle is a square topic. The research methods are documentation, observation, test and interview. The data analysed in this research are students’ activities and students’ achievement score, teacher’s activities. The research show that the student activities attaine 60,38% in the first cycles and 76,95% in second cycles. The teacher activities attaine 75% in the first cycles and 91,66% in second cycles, and  the achievement score attaine 76,40% in the first cycles and 85,22% in second cycles. It can be concluded that the implementation of Student Teams Achievement Division learning model is able to improve student learning outcome.   Key Words: Student Teams Achievement Division, mind mapping, students’ test result, students’ activities.